Rational Expectations, Irrational Exuberance: Linkage between U.S. Investors and Pacific-Basin Stock Returns Rahul Verma - Verma, Rahul (Universiti Utara Malaysia, 2009)
We shed new light on the relevance of rational expectations and irrational exuberance of U.S. individual and institutional investors on Pacific-Basin stock returns.We find insignificant effects of irrational exuberance and significant effect of rational expectations on Asian markets with varying degrees of intensity.There are greater responses of Hong Kong, Malaysia, Philippines, and Singapore while weaker linkages with Taiwan, Thailand, and Korea.Overall evidence suggests that rational expectations of institutional investors are transmitted to a greater extent than those of individual investors.These results are consistent with the view that international effects of the U.S. market can be attributed to rational investor sentiments.